The creation and validation of aptamers binding to murine 3T3-L1 Preadipocytes: preliminary implications for controlled cellular attachment, differentiation and cell fate - Rubidge, Mark Lourens (Rhodes University, Faculty of Science, Biotechnology Innovation Centre, 2017)
The controlled seeding of a variety of stem cells in vitro has been reported to alter the patterns of their subsequent differentiation. This has been attributed to the control of the surface microenvironment onto which adherent stem cells are cultured, especially control of the proximal density of neighbouring cells. Simultaneously, advances in the generation of aptamers - synthetic ligand molecules developed using in vitro selection techniques targeting complex molecules - have aided in the production of molecules capable of selectively binding to a variety of commercial stem cell lines. Combining the aforementioned research fields, the project reported in this thesis aimed to generate DNA-based aptamers capable of assisting with the selective binding of murine 3T3- L1 preadipocytes to a solid surface. This was performed with a view to, eventually, control the seeding densities of the adherent preadipocytes on the surface of the tissue culture dish in subsequent researchers. In the process of meeting this goal, several optimisations of the in vitro process by which aptamers binding to cells are generated (Cell-SELEX) were performed: an analysis into a variety of methods used for the removal of the single stranded aptamer candidate sequences attached to the surface of 3T3-L1 preadipocytes, a comparison of methods for the generation of single-stranded aptamer sequences from double-stranded DNA template molecules and a method for quantifying the removed ssDNA from the cell surface. Their use is further reported in this work. Initially, it was determined that a fluorimetric evaluation of the unbound single stranded DNA was the optimum technique to use to evaluate the relative amounts of aptamer DNA binding to target cells during cell-SELEX; this arose from the release of DNA, and other cell lysate contaminates, which interfered UV/ Vis quantification. The evaluation into different methods of ssDNA removal from the cell surface showed that although trypsinisation of the cells demonstrated the highest level of aptamer detachment (quantified by fluorimetry), there is a decrease the number of potential targets that aptamers could attach to. The most common method for detaching bound DNA aptamer molecules from cellular targets reported in literature, the use of high temperatures, was selected for cell-SELEX to increase the variability in potential target sites on the cell surface. Using techniques optimised in this work, fluorescently-tagged single-stranded oligonucleotide aptamers were later generated with a positive selection pressure to bind to the surface of the 3T3-L1 preadipocytes, but not to their differentiated adipocyte counterparts. After eight cycles of cell-SELEX, fluorescent spectroscopic analysis depicted a 74 % binding retention of the selection pool in the positive preadipocyte selection pool, as opposed to a 0.69 % binding of sequences to the negative differentiated preadipocytes. Following the isolation and identification of candidate sequences, seven separate sequences were identified as being successfully generated from the selection process. Bioinformatic characterisation of these placed sequenced aptamer candidates into two separate families, that were then analysed in opposition to each for their binding affinity toward each other. Using fluorescently-tagged sequences, the binding selectivity of the generated aptamers was validated using both epifluorescent microscopy and confocal microscopy. At this stage, an aptamer sequence selected from prior in-house research to serve as a negative control also demonstrated significant binding to the extracellular matrix of both preadipocytes and mature adipocytes. 5'-thiolated aptamer sequences were used to form self-assembled monolayers on the electrode surfaces of the impedimetric Roche xCELLigence Real-Time Cell Analysis. The use of aptamer sequences to capture the seeded preadipocytes, demonstrated a slight increase in the extent of binding of the preadipocytes to the gold electrode surface and produced some preliminary indications of alterations to the pattern and rate of subsequent differentiation in the preadipocytes. This provides preliminary evidence that aptamers developed to bind specifically to a stem cell line in vitro show potential to be used as to capture said cell when cast in a self- assembled monolayer assembly. This provides a future opportunity to control the seeding densities of the cells in vitro. The effects of cellular differentiation at a set of predefined cellular densities can be demonstrated on a desired stem cell line.
Keywords: Oligonucleotides; Fat cells; Stem cells; Ligand binding (Biochemistry); Fluorimetry